Enduring image : capturing defining moments in crises - Ho, Benjamin (2014)
In today's media environment, crises are magnified as media events and are rich sites for the inception of images. Particular images, like a photograph or a sound bite are found to endure as representations of defining moments of crises. This study seeks to examine the concept of an enduring image, how it is engendered and how it impacts crisis communication efforts. The study utilizes five case studies of crisis with an inherent enduring image. An enduring image constitutes a prime representation of the accused in a given crisis. These images are loaded with symbolic potential and exhibit a sense of permanence in public consciousness. Understanding the implications of an enduring image can offer insights to organizations on how to better manage one's public and media image during or after a crisis. The study is arguably the first in examining the significance and potency of enduring images in crises.